Computed tomographic examination of South American sea lions (Otaria flavescens) with suspected Mycobacterium pinnipedii infection - Jurczynski, Kerstin; Scharpegge, J.; Ley-Zaporozhan, J.; Ley, S.; Cracknell, J.; Lyashchenko, K.; Greenwald, R.; Schenk, Jens-Peter (Vet record, 2011)
Ten South American sea lions (Otaria flavescens) were presented for clinical evaluation and diagnosis of tuberculosis following known exposure to Mycobacterium pinnipedii. CT was used to determine whether foci of calcification in mediastinal lymph nodes, typically associated with pinniped tuberculosis, could be detected and whether CT was a useful diagnostic modality, in conjunction with other tests, for the diagnosis of tuberculosis in this species. Blood was collected from the caudal gluteal vein of each animal for serological testing using commercially available serological tests (ElephantTB STAT-PAK and DPP Vet; Chembio Diagnostic Systems) and a multiantigen print immunoassay (MAPIA), carried out at Chembio to verify the in-house kits. In four of nine animals that underwent CT scanning, lesions consistent with pinniped tuberculosis were apparent and these were confirmed at subsequent postmortem examination. The five remaining animals did not show any abnormalities on CT, with three being negative on serological tests, which were considered to be normal and potentially used as reference images for healthy sea lions. One animal could not be CT scanned due to its large size and weight (510 kg).
Gesehen am 06.07.2022